Performance Evaluation of Hospital Waste Ash-Modified Asphalt Mixtures - Daniel Oguntayo; Olumide Ogundipe; Oluwasegun Aladegboye; Gabriel Ogunkunbi; Yusuf Babatunde; Olawale Aransiola (Advances in Civil Engineering)
Using waste materials in road construction is a sustainable technique that will promote waste reduction, a cleaner environment, cost savings in road construction projects, and serve as an alternative material. This study evaluated the performance of hospital waste ash (HWA) modified asphalt mixtures. The modified asphalt mixtures were produced using HWA as mineral filler at 0%–100% at an interval of 10% by weight. The performance of the mixtures was evaluated with the Marshall, Cantabro, and retained strength index (RSI) tests. The Marshall parameters indicate that the modified asphalt mixtures met the General Specification for Roads and Bridges of Nigeria with satisfactory results. Except for mixes prepared with 90% and 100%, HWA-modified mixtures fulfill the RSI and Cantabro durability requirement at up to 80% filler content. However, to ensure the optimum performance of the HWA-modified asphalt mixtures, a 40% HWA is recommended.